Characteristics and seasonal variation of microplastics in the wastewater treatment plant: The case of Bursa deep sea discharge - Can, Tugba; Ustuen, Gokhan Ekrem; Kaya, Yunus (Pergamon-Elsevier Science Ltd, 2023)
Microplastics (MPs) are an emerging pollutant that can be detected in all ecosystems, especially aquatic ecosystems. Wastewater treatment plants (WWTPs) are important point sources of MP release into the sea. In this study, the characteristics of MPs in wastewater and sludge samples taken from different units of WWTP in BursaGemlik district for 12 months were investigated. Wastewater and sludge samples collected from 7 different points were classified as size, shape, color, and counted. The amount of MP in the influent and effluent of the WWTP, respectively; 107.1 & PLUSMN; 40.2 MP/L and 4.1 & PLUSMN; 1.1 MP/L. Although the MP removal efficiency of the WWTP is 96.17 %, approximately 74,825,000 MP is discharged into the Marmara Sea every day. The amount of MP in the sludge is 14.3 & PLUSMN; 7.1 MP/g. The amount of MP accumulated in 22tons of waste sludge formed daily in WWTP was calculated as 314,600,000 MP, and the annual accumulated amount was calculated as approximately 1.15 x 1011 MP. The MPs in the WWTP were mainly 1-0.5 mm in size. Fibers were the dominant MP shape in both the wastewater and sludge samples. Black and transparent were the dominant MP colors. Seven different polymer types of MPs were detected, which were mainly types of polyethylene, polypropylene, and polyethylene terephthalate. Despite the high removal efficiency in the investigated WWTP, it has been shown that it acts as an important source of MPs to the sea ecosystem due to the high discharge rates.
Keywords: Microplastics; Wastewater treatment plant; Sludge; Characteristics; Seasonal variation